The origins of modern humans - Smith, Fred H.; Ahern, James C. M.
"This work provides an update of an award-winning classic, which introduced the major competing theories in human evolution. The coverage now features new fossil and molecular evidence, such as the genetic evidence including evolutionary inferences drawn from assesments of modern humans and large segments of the genome of the Neanderthal. The inclusion of younger scholars also enhances the work, leading to a comprehensive and vibrant current edition"--
"In 1984, Fred Smith and Frank Spencer introduced The Origins of Modern Humans: A World Survey of the Fossil Evidence, a volume which introduced two of the major theories of human evolution that would be debated for the next twenty years. The book went on to win Best Book in the Life Sciences 1984. Now Smith, with Jim Ahern, has compiled the second edition of this field classic, incorporating the latest information in paleontological, genetic and developmental biology to pick up where the first edition left off and push the debate forward for the next twenty years"--
Keywords: Human evolution; SCIENCE / Life Sciences / Evolution